2000
DOI: 10.1097/00006676-200008000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Increases the Risk of Pancreatic Calcification in Late-Onset But Not Early-Onset Idiopathic Chronic Pancreatitis

Abstract: An association exists between cigarette smoking and pancreatitis owing to alcohol. We determined whether cigarette smoking affected the course of pancreatic calcification and insufficiency in idiopathic chronic pancreatitis. Medical records were analyzed of 24 persons with early- and 42 with late-onset idiopathic chronic pancreatitis who were diagnosed between 1976 and 1982 and then followed prospectively until 1985. Smoking equaled >5 pack-years before calcification or insufficiency or last follow-up. Mean fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
3
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 18 publications
8
46
3
4
Order By: Relevance
“…32 However, Imoto et al concluded that smoking did not affect DM development. 33 In our study, we did not find smoking as a risk factor for increasing the risk of DM in CP, though a significant difference in DM development was only found between smokers and non-smokers in univariate analysis (P ¼ 0.02).…”
Section: Discussioncontrasting
confidence: 68%
“…32 However, Imoto et al concluded that smoking did not affect DM development. 33 In our study, we did not find smoking as a risk factor for increasing the risk of DM in CP, though a significant difference in DM development was only found between smokers and non-smokers in univariate analysis (P ¼ 0.02).…”
Section: Discussioncontrasting
confidence: 68%
“…In addition, smoking increases the risks of developing chronic pancreatitis and pancreatic calcification. Abstinence from smoking may prevent the progression of chronic pancreatitis; therefore, giving smoking cessation guidance is recommended [66][67][68].…”
Section: Lifestyle Guidancementioning
confidence: 99%
“…Moreover, alcohol withdrawal is quite often not associated with smoking withdrawal. Retrospective data indicated a beneficial effect of smoking withdrawal to reduce/avoid pain and complications in chronic pancreatitis [32,33]. Experts recommend smoking withdrawal for patients with chronic pancreatitis [18].…”
Section: C3mentioning
confidence: 99%